Sistem Penentuan Lokasi Menara Base Transceiver Station dengan Algoritma AHP-TOPSIS - Amar, Muh. Ikhsan; Ramdana, Ramdana; DA, Alvian Tri Putra (Forum Kerjasama Pendidikan Tinggi, 2022)
Cellular telecommunication technology has now become an inseparable part of the increasingly mobile pattern of human life, this of course has an impact on the number of uses of cellular telecommunication technology which is increasing every day. This increase has encouraged cellular telecommunications technology vendors to continuously improve the quantity and quality of their telecommunications networks by establishing telecommunications equipment such as Base Transceiver Station (BTS) towers at strategic points. This study aims to build a system for determining the location of BTS towers that can provide visualization of information on the distribution of existing BTS towers and their coverage area radius. Analysis and location determination using a combination of AHP and TOPSIS methods. The AHP method is used to determine the objectivity of the weight and importance of the BTS tower location criteria. Furthermore, the results of the comparison of criteria will be used in the TOPSIS method to assess the rating of each candidate location. The results of the study obtained that the criteria for the location of BTS towers were population density with a weight of 0.42, the distance of the existing tower was 0.2, location access was 0.31, and the installation cost was 0.08. Meanwhile, the candidate locations were measured using linguistic variables with a weight of 0.67 for very good criteria, 0.23 for good, and 0.10 for good enough. System testing was carried out on determining the location of the BTS tower in Sinjai Borong District by analyzing three candidate locations and the results obtained that the Samaenre location was the best candidate with a rating value of 0.74.